EFEKTIVITAS PEMBELAJARAN SENI RUPA MELALUI PENERAPAN MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN MINAT BERKARYA PESERTA DIDIK - Hadikusuma, Risman (Nuansa Journal of Arts and Design, 2025)
This study aims to describe the effectiveness of visual art learning through the implementation of the Project-Based Learning (PjBL) model in enhancing students' interest in creating artworks. This research employs Classroom Action Research (CAR) methodology conducted at SMA Negeri 9 Makassar. The results show that the application of the PjBL model is highly effective in fostering students' interest in creating artworks. PjBL proves to be a learning model that aligns with the characteristics, needs, and learning styles of students. This model teaches students to collaborate, take responsibility, and work independently to complete their projects. Additionally, the study highlights a supporting learning strategy to enhance students' interest in creating artworks, namely the implementation of an outing class learning strategy. This strategy is essentially understood as learning conducted outside the classroom. Students benefit greatly from the actualization of the outing class strategy, including fostering a love for nature and their environment, stimulating their creativity and imagination, and increasing their motivation through direct interaction with nature. In this study, the author assigned a project task to create educational posters. Through this project task, students gained meaningful learning experiences and the values of the Pancasila student profile, such as collaboration, independence, teamwork, discipline, and the spirit of mutual cooperation.